A CASE OF UNIHEMISPHERIC PROGRESSIVE MULTIPLE SCLEROSIS. (29th November 2012) - Furby, J; Giovannoni, G; Page, R
Abstract : We present the case of a 52 year old lady who now has a 2 year history of a progressive left hemiplegia and hemisensory disturbance. Examination has demonstrated isolated left sided upper motor neuron signs of the face, arm and leg throughout her illness. Initial MRI revealed a high T2 signal region of white matter abnormality adjacent to the posterior horn of the right lateral ventricle with minimal enhancement. Over time this area of abnormality has evolved and spread anteriorly into the basal ganglia, and is associated with the development of hemiatrophy. The rest of the brain and spinal cord has remained of normal appearance. Brain biopsy of the abnormal region revealed a well demarcated zone of demyelination with gliosis and an inflammatory cell infiltrate, features that are compatible with a diagnosis of multiple sclerosis. Further investigation for other causes of central nervous system demyelination has been negative and unmatched oligoclonal bands were detected in the spinal fluid. Trimodal evoked potentials only demonstrated involvement sensory tracts from the left side. The clinical, radiological and pathological features of this case suggest a diagnosis of primary progressive multiple sclerosis; dissemination in time and space with no other cause found. Cases of a focal progressive neurological deficit have been described secondary to an inflammatory cord or brainstem lesion but here we demonstrate a progressive unilateral deficit in association with an unusual evolving right hemisphere region of demyelination.